Trypanosomosis: A priority disease in tsetse-challenged areas of Burkina Faso - Soudre, A.; Ouédraogo-Koné, S.; Wurzinger, Maria; Muller, S.; Hanotte, Olivier H.; Ouédraogo, A.G.; Sölkner, Johann (Springer, 2013)
Trypanosomosis is an important disease affecting humans as well as animals. It remains a big constraint to livestock productions in tropical areas. The objective of this study was to assess the importance of trypanosomosis among cattle diseases in Burkina Faso, mainly in tsetse-challenged areas, and to capture information on how farmers apply available methods for controlling the disease. A survey has been carried out in 29 villages of Burkina Faso in three regions (north, southwest, and west regions). One hundred and thirty-four cattle breeders were interviewed individually with a questionnaire. The results indicate that among the 16 diseases mentioned by cattle breeders, trypanosomosis is the most important one in tsetse-challenged areas. Overall, 76.12 % of the breeders mentioned it as the most important disease, while 54.55 % of the farmers in the southwest region and 70.91 % of the farmers in the west region ranked it as a priority disease. Chemoprophylaxis/chemotherapy is widely used as a control method. Isometamidium chloride and diminazene aceturate were used by 53.49 and 46.52 % of the responders, respectively. Among farmers, 85.55 % ranked diminazene aceturate as the less efficient while 14.45 % ranked isometamidium chloride as the most efficient trypanocid. Trypanocidal drug quality and drug resistance were raised as a major concern by 30.77 and 50 % of the respondents, respectively. According to them, zebu cattle are more susceptible to trypanosomosis than taurine Baoule cattle and their crosses with zebu, emphasizing that crossing susceptible breeds with trypanotolerant ones, could be used as part of an integrated control strategy.